2021
DOI: 10.1007/s11205-021-02699-3
|View full text |Cite
|
Sign up to set email alerts
|

COVID Health Structure Index: The Vulnerability of Brazilian Microregions

Abstract: Many developing countries have highly unequal health systems across their regions. The pandemic of COVID-19 brought an additional challenge, as hospital structures equipped with doctors, intensive care units and respirators are not available to a sufficient extent in all regions. Using Data Envelopment Analysis, we create a COVID Index to verify whether the hospital structures in 543 Brazilian microregions are adequate to deal with COVID-19 and to verify whether public policies were implemented in the right di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 65 publications
(55 reference statements)
3
15
0
Order By: Relevance
“…For the relaxation phase , government effectiveness is positively associated with the efficiency score, this emphasizing, once again, the relevance of making appropriate decisions in the moments that require such actions; instead, it seems that cultural factors such as power distance negatively influence the efficiency of health systems, which means that there are variations in compliance with safety measures depending on inequalities in society (related to education, income, etc.). Our results are similar to those obtained by [ 9 , 14 , 16 , 28 , 29 ], for which show that the prompt and effective intervention of governments and the adherence of the population to these measures were decisive factors in combating COVID-19.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…For the relaxation phase , government effectiveness is positively associated with the efficiency score, this emphasizing, once again, the relevance of making appropriate decisions in the moments that require such actions; instead, it seems that cultural factors such as power distance negatively influence the efficiency of health systems, which means that there are variations in compliance with safety measures depending on inequalities in society (related to education, income, etc.). Our results are similar to those obtained by [ 9 , 14 , 16 , 28 , 29 ], for which show that the prompt and effective intervention of governments and the adherence of the population to these measures were decisive factors in combating COVID-19.…”
Section: Resultssupporting
confidence: 90%
“…The other independent variables do not influence the efficiency score, having a significance threshold higher than 0.05. The results obtained are similar to those of [ 9 , 15 , 18 , 20 , 21 , 25 , 29 ] which showed that the effects of COVID-19 were stronger among the elderly and sick population.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…As Pakistan is a developing and highly populated country with insufficient economic condition and poor healthcare system. Studies showed that disease outbreaks greatly challenge the health infrastructure of the countries for instance insufficient health policies, lack of health care system, weak governance and general public risking attitude towards preventative measures, increased the likelihood for worst scenario [19][20][21][22][23] . Firouzbakht, Omidvar [24] conducted a web-based survey to assess the factor affecting the COVID-19 preventative behaviour and concluded that 50% of the respondents have not taken seriously, the COVID-19 preventative measures i.e., wearing mask, washing hand and wearing gloves.…”
Section: Discussionmentioning
confidence: 99%